Pemerolehan Bahasa dalam Mengenal Kosakata Warna pada Anak Usia Dini 3-5 Tahun di PAUD An-Najah Rowosari Semarang - Putri Naura Nadzifa Hasyim; Asep Purwo Yudi Utomo (Lembaga Pengembangan Kinerja Dosen, 2025)
Language acquisition is a fundamental aspect of early childhood development, particularly in learning color vocabulary, which plays a crucial role in cognitive, linguistic, and social growth. However, empirical data show that approximately 47.3% of Indonesian children aged 3-5 experience delays in recognizing colors, potentially hindering their overall language and cognitive development. This study aims to analyze the process of language acquisition in learning color vocabulary among children aged 3-5 years using a psycholinguistic approach, as well as to explore teaching methods employed by teachers at PAUD An-Najah Rowosari Tembalang, Semarang. A qualitative descriptive method was used, involving 20 children, teachers, and parents as informants. Data were collected through observation, interviews, and documentation. The results reveal variations in color vocabulary acquisition: 30% of children showed significant progress, 50% demonstrated good development, and 20% required intensive assistance. Influencing factors include home stimulation, teaching methods, and psychological aspects of the children. This research enriches psycholinguistic studies, supports the development of effective teaching methods, and provides guidance for parents and educators in fostering early childhood language development, especially in color recognition.